The effect of sol-gel technique on the silicon carbide particulate - 383701 Ng, June Nee (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Materials)) - Universiti Teknologi Malaysia, 2003